LAWS ON THE ASSIGNMENT TO CLERICAL SERVICE IN TURKESTAN (BASED ON MATERIALS FROM THE GOVERNOR-GENERAL'S OFFICE) (American Journal of Research in Humanities and Social Sciences, 2024)
Source study of the history of the Chancellery of the Governor-General in Turkestan requires the analysis of a large number of documents to establish the objective reasons for the activities of the executive body. This article analyzes information about the laws on appointment to church service in Turkestan.